2014
DOI: 10.1111/tpj.12536
|View full text |Cite
|
Sign up to set email alerts
|

β‐Carboxysomal proteins assemble into highly organized structures in Nicotiana chloroplasts

Abstract: SUMMARY Photosynthetic efficiency of C3 plants suffers from the reaction of ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) with O2 instead of CO2, leading to the costly process of photorespiration. Increasing the concentration of CO2 around Rubisco is a strategy used by photosynthetic prokaryotes such as cyanobacteria for more efficient incorporation of inorganic carbon. Engineering the cyanobacterial CO2 concentrating mechanism, the carboxysome, into chloroplasts is an approach to enhance photosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
113
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 51 publications
4
113
0
1
Order By: Relevance
“…Previous attempts to engineer BMCs have focused on associating heterologous proteins to shells using EPs. For example, through the addition of two different EPs to pyruvate decarboxylase and alcohol dehydrogenase, Lawrence et al (2014) were able to repurpose a propanediol utilization compartment shell for ethanol production; Lin et al (2014b) showed that the encapsulation peptide from CcmN targets yellow fluorescent protein into carboxysome-like structures formed in mutant wild tobacco (Nicotiana benthamiana) plants. In contrast, the approach reported here focuses on assembling a multifunctional BMC core: CcmC nucleates Rubisco, supplies CA activity, and recruits the shell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous attempts to engineer BMCs have focused on associating heterologous proteins to shells using EPs. For example, through the addition of two different EPs to pyruvate decarboxylase and alcohol dehydrogenase, Lawrence et al (2014) were able to repurpose a propanediol utilization compartment shell for ethanol production; Lin et al (2014b) showed that the encapsulation peptide from CcmN targets yellow fluorescent protein into carboxysome-like structures formed in mutant wild tobacco (Nicotiana benthamiana) plants. In contrast, the approach reported here focuses on assembling a multifunctional BMC core: CcmC nucleates Rubisco, supplies CA activity, and recruits the shell.…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts have led to important advances in expressing the b-carboxysome shell and cyanobacterial form 1B Rubisco in chloroplasts (Lin et al, 2014a(Lin et al, , 2014b, which represent the first steps in assembling carboxysomes in plants. More broadly, these results bode well for the prospect of engineering novel types of metabolic nanoreactors based on BMC architectures in heterologous systems (Frank et al, 2013), including cyanobacteria and other microbial platforms for renewable chemical and biofuel production.…”
Section: Introductionmentioning
confidence: 99%
“…Then we mixed the culture expressing GFP N to another culture expressing GFP C in equal volume to a final optical density of 0.5 each and incubated the mixtures in the dark at 28°C for about three hours. Afterward, these mixtures were used to infiltrate leaves from 4-to 6-week-old Nicotiana benthamiana plants grown at 10 h of light per day as described in Lin et al (2014). Within 2 to 4 d after agroinfiltration, the leaf tissues were examined with a confocal microscope (Zeiss LSM 710) through a LD LCI Plan-Apochromat 253/0.8 Imm Korr DIC M27 objective.…”
Section: Bimolecular Fluorescence Complementation Assaymentioning
confidence: 99%
“…For example, introducing b-carboxysomes into higher plants that use the ancestral C 3 pathway of photosynthesis could potentially enhance photosynthetic carbon fixation and crop production (Lin et al, 2014a(Lin et al, , 2014b. However, engineering of functional carboxysomes requires extensive understanding about the principles underlying the formation of b-carboxysomes and the physiological integration of b-carboxysomes into the cellular metabolism.…”
mentioning
confidence: 99%